A CLOCK THAT SHOWS TIME IN TWO DIFFERENT PLACES AT THE SAME TIME - Mukhammadjon Turgunovich Xalilov (Zeta Repository, 2023)
This article presents ideas about the construction of a watch that simultaneously shows the user's permanent residence and temporary residence (on a trip, as a tourist, travel) and constructive solutions to the problem.